TRACKING DEVICES ON COLLATERAL VEHICLES BY FINANCIAL INSTITUTIONS INVADES CUSTOMER PRIVACY ACCORDING TO PRIVACY PROTECTION LAW - Suwinto Johan (Journal of Law and Policy Transformation, 2023)
Financial institutions expect financing to be returned on time and adhere the terms of the agreement. Financial institutions profit from the ability to handle non-performing loans (NPL). The lower the level of NPL, the lower the risk and the higher the profit made by the financial institution. One way to mitigate risk is the capacity to take over the collateral for financing. One of the collaterals for financing is in the form of a vehicle. This vehicle is guaranteed by Fiduciary security. If consumer default occurs, financial institutions can seize the collateral and use it to pay off the loan. Financial institutions employ a variety of strategies to ensure that collateral is quickly located in the event of a default. One method is to use technology to install a tracking device. This study scrutinizes the use of tracking devices by financial institutions from the perspective of consumer privacy protection. This normative legal research concludes that collaterals with Fiduciary security are property of financial institutions prior to settlement. However, the installation of tracking devices on collateral vehicles might invade customer privacy. The customer has the option to object the installation of the device on the vehicle.